IDDF2022-ABS-0030 Implementing a database to track patients' compliance in the high-risk pancreatic cancer clinic. (2nd September 2022) - Foley, Rebecca; Boucher, Jean; LaFemina, Jennifer; Arney, Luke; Chuprin, Jane; Whalen, Giles; Lindberg, James; Fain, James
Abstract : Background: Pancreatic cancer is projected to become the second leading cause of cancer death in the United States by 2030. Screening of high-risk individuals (HRI's) using endoscopic ultrasound (EUS) or magnetic resonance imaging (MRI), specifically magnetic resonance cholangiopancreatography (MRCP), saves lives and reduces morbidity and mortality. Screening can detect surgically resectable lesions, which is key to survival since most lesions present as unresectable or metastatic. The specific aims of this project were to address the quality improvement process to track adherence of the patients who participate in the high-risk pancreatic cancer clinic at UMass Memorial Healthcare. Methods: Patients deemed to be high risk according to the Cancer of the Pancreas Screening (CAPS) Consortium Guidelines included having at least one first-degree relative with a diagnosis of pancreatic cancer, a genetic mutation that places them at higher risk for pancreatic cancer, or both are the cohort. The data was collected via EMR using REDCap, a secure web application to analyze high-risk patients' adherence with yearly screening. The method utilized a quality improvement project design. Results: Results demonstrated a majority of participants were female, 53% had a first-degree relative with pancreatic cancer, a majority of participants did not carry a genetic mutation while the highest mutation finding included 16 participants (14.4%) with a BRCA 2 gene mutation. A majority of participants, 64.9% (n=72) were non-compliant with screening while 35% (n=39) had yearly screening. Participants who were non-adherent with screening endorsed multiple factors for non-adherence including not believing surveillance was necessary, not qualifying for screening at the time of initial appointment, not receiving reminder phone calls for clinic appointments and surveillance imaging, other health concerns, high insurance deductibles, the COVID pandemic, and high anxiety. Conclusions: Mitigation of the reasons for non-adherence is a crucial practice implication. Patient education regarding the importance of long-term yearly screening and teaching patients self-efficacy behaviors may improve screening adherence. Prospectively analyzing compliance will reduce missed care opportunities. Health care policies must be amended to require insurance companies to cover the screening of HRI's.